Trekk fra handelsforbindelser mellom Nord Norgeog havner ved Østersjøen i 2. del av 1800-tallet - Wiśniewska, Olga (Folia Scandinavica Posnaniensia, 2007)
The contacts between the Prussian Baltic ports with Norway have a centuries old tradition. The Northern Scandinavia was a vital source of fish products, such as; salted and desiccated cod, codliver oil or hard roe. They, in turn, were considered to be the most significant ingredients of the diet of the people inhabiting the middle-east Europe. Moreover, ports such as Gdańsk and Szczecin constituted the essential links on the trade routes between Norway and Europe. In the middle of the 19th century, due to the Industrial Revolution and, most of all, the invention of the telegraph and steam ships, the trade ties between geographically remoted contracting parties were tightened. Consequently, the trade centers such as Bergen and Copenhagen ceased to mediate. What is more, the credit system and keeping the market analyzes were modernized. The marriage of Margrete von Niemirsky from Gdańsk with the well-off merchant from Tromsø may be the example of such close contacts of the Prussian ports with the Far North. As another example may serve the history of the staemer which was the private initiative of the merchant Zahl, Kjærringøy, aiming to bring closer the Northern Norway and the Baltic sea.